Climate control since 6 ka and human impact on landscapes near Starorechenskoye fortress (Russian South Far East): From Bohai farmers to modern agrocomplexes. (June 2021) - Razjigaeva, Nadezhda G.; Ganzey, Larisa A.; Grebennikova, Tatiana A.; Kornyushenko, Tatiana V.; Ganzei, Kirill S.; Kudryavtseva, Ekaterina P.; Belova, Irina V.; Klyuev, Nikolai A.; Prokopets, Stanislav D.
Abstract: Multi-proxy studies of floodplain sequences provided materials for reconstructing natural and anthropogenic factors affecting landscape evolution of the Razdolnaya (Suifun) River basin near the Starorechenskoye settlement attributed to the Bohai culture in the Russian Far East. Data were obtained on the humid phase of the middle Holocene (~5.9 ka), while the last 2.5 ka were studied in detail. The vegetation development tracked climate conditions, largely changed in moisture. The studied sequences include a paleosol that developed during a prolonged period of drought 2.7-1.3 ka ago. The period was noted for a wide occurrence of steppe and forb meadows with wormwood, and open birch forests. The climate became gradually warmer since the late 7th to 10th centuries CE following by a decrease in temperature and high humidity in the Little Ice Age. The pollen assemblages display an appearance of dark conifers and Korean pine pollen brought by floods. In Pinus densiflora and birches gained in importance in the mountain forests. The pollen spectra from surface soil are indicative of the wide development of agricultural landscapes. The recorded biological indicators shed light onto the dynamics of paleo-floods. The significance of anthropogenic factors in landscape evolution is considered with reference to the periods of the Bohai settlers, first settlers in 19th–early 20th centuries, and the present days marked with development of the modern agrocomplexes. Highlights: The reconstructions were based on the multiproxy study of flood-plain sequences. The most important of the natural factor appears to be contrast in moisture supply. Prolonged period of drought 2.7-1.3 ka ago was recorded. Bohai settlers impact on the environments was minimal. A radical transformation began since the penetration of settlers at 19th century.